A SYSTEMATIC APPROACH IN MODERN INTERDISCIPLINARY RESEARCH - Nurmamatova Sevara Kamol qizi,; Ruzmetova Diana Komilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This paper explores the importance of the systemic perspective in contemporary interdisciplinary research. It outlines how systemic thinking facilitates the integration of  various  scientific  disciplines,  the  examination  of  complex  structures,  and  the comprehension of multi-tiered interactions within natural, social, and technological frameworks.  Furthermore,  the  article  presents  instances  of  systemic  methodology employed in current scientific fields and highlights its benefits for fostering innovative and sustainable solutions.